Comparative Analysis of Provincial Government Financial Performance on the Island of Java in the Post-Pandemic Period (2021–2024) Based on Financial Ratios - Ahmad Haetami; Budi Firmansyah (LP2M IAIN Palopo, 2026)
This study examines how provincial governments in Java Island performed financially during the post-pandemic period of 2021–2024 and whether meaningful differences exist across provinces. The study plays a comparative and inter-temporal role by evaluating fiscal capacity and expenditure structure using regional financial ratios derived from Budget Realization Reports of six provincial governments. The data show that fiscal independence and the effectiveness of local own-source revenue generally improved after the pandemic, but large disparities among provinces persist. Dependency on intergovernmental transfers remains structurally significant. The analysis discusses the results through descriptive comparison across provinces and annual trends, focusing on the interaction between revenue recovery and expenditure management. The main finding indicates that post-pandemic fiscal recovery in Java’s provincial governments is driven primarily by revenue performance, while expenditure quality and capital spending structure have not improved proportionally, suggesting that fiscal strengthening has not yet been translated into more development-oriented budget allocation.